A Bibliometric Analysis of Islamic Philanthropy - Muhammad Afiat Anang Luqmana; Eva Nurul Huda; Achmad Tohirin (Universitas Muhammadiyah Yogyakarta, 2023)
This study aims to retrieve journal articles related to Islamic philanthropy over a span of 16 years and propose new pathways for future research. The study involved a bibliometric analysis of 122 publications on the subject registered in the Scopus database from 2007 to 2023. The bibliometric procedure evaluates research performance and progress within an international impact framework, while Biblioshiny-R and VOSviewer visualize overall research trends in Islamic philanthropy. The results of the study show that Indonesia is the country with the most publications related to Islamic philanthropy. Hilman Latief and Fauzia Amalia are the two leading authors in this field based on the total number of publications and citations. The Journal of Muslim Philanthropy and Civil Society is the journal that has published the most papers on this topic. Some of the author's most recent keywords include